Increased sea ice concentration worsens fledging condition and juvenile survival in a pagophilic seabird, the snow petrel. (25th July 2018) - Sauser, Christophe; Delord, Karine; Barbraud, Christophe
Abstract : Polar sea ice is changing rapidly, threatening many taxa in the Arctic and the Antarctic. Little is known about the effects of sea ice on early life-history traits of sea ice specialist species, although juvenile stages are a critical component of population dynamics and recruitment. We examined how annual variation in sea ice concentration (SIC) affects juvenile survival and body condition at fledging in the snow petrel Pagodroma nivea using long-term datasets encompassing 22 years for body condition and 37 years for juvenile survival. We show that SIC and southern annular mode (SAM), the principal mode of variability of the atmospheric circulation in the Southern Hemisphere, have strong nonlinear effects on juvenile survival and body condition. Below ca 20–30% SIC, body condition remained stable, but decreased almost linearly for higher SIC. Juvenile survival was negatively related to SIC and to SAM during the chick rearing period. We suggest that the base of the sea ice food web would be directly affected by sea ice conditions, thus acting locally on the abundance and structure of prey communities.